Crystalline podocytopathy and tubulopathy without overt glomerular proteinuria in a patient with multiple myeloma - Eun Jeong Lee; Su Yeon Lee; So Young Park; Yonjin Kim; Jae Shin Choi; Mi Jeoung Kim; Ji Hyeon Park; Jung Eun Lee; Ghee Young Kwon; Yoon-Goo Kim (The Korean Society of Nephrology, 2016)
Crystalline nephropathy is a rare yet well-known condition associated with multiple myeloma and other light chain-secreting disorders. Paraproteins that are resistant to proteolysis crystallize within proximal tubular cells and cause light-chain proximal tubulopathy, which presents clinically as Fanconi syndrome. Podocytes are rarely affected, and the crystalline inclusions within podocytes are typically precipitated, yielding significant glomerular proteinuria. Here we report a case of extensive crystalline inclusions primarily within podocytes and proximal tubules that presented only with Fanconi syndrome and renal insufficiency. Despite the presence of extensive crystalline inclusions in podocytes and diffuse foot process effacement, the patient had no clinical evidence suggestive of podocyte injury.